Evaluation of Energy Efficiency and Flexibility in Smart Buildings - Arteconi, Alessia (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue "Evaluation of Energy Efficiency and Flexibility in Smart Buildings" addresses the relevant role of buildings as strategic instruments to improve the efficiency and flexibility of the overall energy system. This role of the built environment is not yet fully developed and exploited and the book content contributes to increasing the general awareness of achievable benefits. In particular, different topics are discussed, such as optimal control, innovative efficient technologies, methodological approaches, and country analysis about energy efficiency and energy flexibility potential of the built environment. The Special Issue offers valuable insights into the most recent research developments worldwide.